2017
DOI: 10.7567/apex.10.031701
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of laser speckle noise suppression by using polymer-stabilized liquid crystals within twisted nematic cell

Abstract: We propose a robust method to suppress laser speckle using a polymer-stabilized liquid crystal (PSLC) device with high initial transmittance. With applied voltage, a large modulation depth has been produced through light scattering because of the refractive index mismatch between the rotated nematic liquid crystals and the polymer networks. By using PSLCs with 5 wt % monomer, a speckle noise reduction rate of approximately 54.7% can be achieved with an applied voltage of 6 V. The lowest speckle contrast of app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…Experimental setup for studying light modulation using a PSLC cell at different values of the control voltage (Ref. [39], Figure 3).…”
Section: Using Colloidal Dispersionmentioning
confidence: 99%
“…Experimental setup for studying light modulation using a PSLC cell at different values of the control voltage (Ref. [39], Figure 3).…”
Section: Using Colloidal Dispersionmentioning
confidence: 99%
“…Liquid crystals (LCs) have been widely used in the display field because of their excellent electro-optical properties and have become ideal fillers for static diffusers. Some research groups have reported studies on speckle reduction by LCs [ [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ] because LC molecules have unique birefringence properties and can be modulated by an electric field. LCs are typically used for speckle reduction in the form of polymer LC composites, in which dynamic transition between the scattering and transparent states can be achieved by voltage control.…”
Section: Introductionmentioning
confidence: 99%
“…However, speckle noise in CT images causes severe visual interference and obscures the image's features [5]. Speckle noise is caused by the interference of ultrasound on human tissues, and its component information is complex.…”
Section: Introductionmentioning
confidence: 99%